Understanding the health challenges of Amazonian riverine communities: A qualitative study on community perceptions amid climatic change - Alícia Patrine Cacau dos Santos; Theo de Lima Guerra; Evellyn Antonieta Rondon Tomé da Silva; Inácio Coelho Sá; Hiran Sátiro Souza da Gama; Ana Paula Silva Oliveira; Rafaela Nunes Dávila; Hélio Afonso Amazonas Júnior; Joaquim da Silva Lopes; Esly Camico Mandu; Tatiana Bacry Cardoza; Jaqueline de Almeida Gonçalves Sachett; et al. (PLoS ONE, 2025)
Background In the Brazilian Amazon, approximately 900,000 people live along riverbanks, relying on the biome for survival and livelihoods. Severe droughts and flooding events, intensified by the El Niño phenomenon and human-driven actions such as deforestation and fires, exacerbate the isolation of traditional communities. This isolation limits access to essential healthcare services and worsens existing health inequalities among vulnerable populations. This study investigates how extreme climatic events impact health and healthcare access in traditional riverine communities, focusing on their perceptions and lived experiences. Methodology/principal findings A qualitative study was conducted in a riverine community in Tabatinga, Western Brazilian Amazon. Thirty-two purposively selected participants (farmers, fishermen, and students) took part in in-depth interviews and focus-group discussions. Thematic analysis was conducted using MAXQDA software. After the analysis two main themes emerged: (1) the impacts of Amazonian seasonality on healthcare access, and (2) the dynamics of arrivals and departures along riverbanks. Participants highlighted health challenges tied to seasonal extremes, including water and food insecurity, financial vulnerability, spikes in gastrointestinal diseases, increased accidents with aquatic or wild animals, river pollution, and higher drowning rates. They also noted births and deaths occurring along riverbanks during extreme events. Most respondents perceived that extreme weather events, especially severe droughts, have intensified over the past decade, worsening health and food/water security and further restricting healthcare access. Conclusions/significance In this scenario, riverine communities are highly vulnerable to climate change, as existing health challenges are compounded by escalating climatic crises. Tailored healthcare solutions, including telemedicine platforms, mobile clinics, and resilient transportation networks, are urgently needed. Investments in communication infrastructure and emergency air transportation are critical as riverine navigation becomes increasingly unreliable.